Transcription factor binding at enhancers: shaping a genomic regulatory landscape in flux - Palstra, Robert-Jan (Frontiers in Genetics, 2012)
The mammalian genome is packed tightly in the nucleus of the cell. This packing is primarily facilitated by histone proteins and results in an ordered organization of the genome in chromosome territories that can be roughly divided in heterochromatic and euchromatic domains. On top of this organization several distinct gene regulatory elements on the same chromosome or other chromosomes are thought to dynamically communicate via chromatin looping. Advances in genome-wide technologies have revealed the existence of a plethora of these regulatory elements in various eukaryotic genomes. These regulatory elements are defined by particular in vitro assays as promoters, enhancers, insulators and boundary elements. However, recent studies indicate that the in vivo distinction between these elements is often less strict. Regulatory elements are bound by a mixture of common and lineage specific transcription factors which mediate the long-range interactions between these elements. Inappropriate modulation of the binding of these transcription factors can alter the interactions between regulatory elements, which in turn leads to aberrant gene expression with disease as an ultimate consequence. Here we discuss the bi-modal behavior of regulatory elements that act in cis (with a focus on enhancers), how their activity is modulated by transcription factor binding and the effect this has on gene regulation.